Pour en finir avec les Monomanes de Géricault : considérons leur rôle dans la construction du mythe de l’artiste - Jubinville, Ginette (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2016)
Théodore Géricault’s Monomanes (Portraits of the Insane ; 1820s) were rediscovered in 1863, just four years before his first biography was published. This article examines this previously unstudied conjuncture in order to put to rest some of the myths surrounding these works and to show that their circulation contributed to the discourse on Géricault that was taking shape at the time. These five portraits have been described as displaying a duality that places them between art and psychiatry, between science and popular culture. This article argues that this resulted from the amalgamation of two distinct understandings of monomania : the scientific one at the time of their production and the popular one at the time of their rediscovery.